1997
DOI: 10.1002/(sici)1099-1344(199704)39:4<291::aid-jlcr973>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Direct tritium labeling of multifunctional compounds using organoiridium catalysis

Abstract: The tritium exchange labeling of a variety of complex compounds is achieved in the presence of catalyst precursor [(cod)Ir(PPh3)2]BF4 and limited amounts of tritium gas. The regioselectivity of exchange is high and consistent with empirical rules previously observed. High specific activity levels are often achieved, usually with specific aryl C‐H bonds. However, remarkably efficient exchange occurs in certain N‐alkyl groups. Studies of intermolecular inhibition of catalytic exchange suggest reasons why larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…It was previously reported that heteroaryl nitrogen ligand such as pyridine and pyrimidine can effectively mediate hydrogen isotope exchange at sp 3 carbons, and its mediating functions are also more effective than amide carbonyls . After further analyzing the structure of PF‐622 , it is possible that quinoline's nitrogen can direct the H‐T exchange of 3,5‐positions (sp 3 carbon) of the piperazine moiety (ring B) in the in situ assembling agostic complexes ( 5a ) and then iridium 6‐membered metallacycle ( 5a ′).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that heteroaryl nitrogen ligand such as pyridine and pyrimidine can effectively mediate hydrogen isotope exchange at sp 3 carbons, and its mediating functions are also more effective than amide carbonyls . After further analyzing the structure of PF‐622 , it is possible that quinoline's nitrogen can direct the H‐T exchange of 3,5‐positions (sp 3 carbon) of the piperazine moiety (ring B) in the in situ assembling agostic complexes ( 5a ) and then iridium 6‐membered metallacycle ( 5a ′).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that heteroaryl nitrogen ligand such as pyridine and pyrimidine can effectively mediate hydrogen isotope exchange at sp 3 carbons, 6,16,18 and its mediating functions are also more effective than amide carbonyls. 6,17 After further analyzing the structure of PF-622, it is possible that quinoline's nitrogen can direct the H-T exchange of 3,5-positions (sp 3 carbon) of the piperazine moiety (ring B) in the in situ assembling agostic complexes (5a) and then iridium 6-membered metallacycle (5a′). The carbonyl group of the urea moiety is in similar distance to aromatic (orthocarbon ring A) and aliphatic (C3 and C5 ring B) carbons, but the carbonyl group participation of the direction of H-T exchange at sp 3 carbon may be unlikely because previous research data 17 show that the quinoline's nitrogen coordinates the iridium center more effectively than aminocarbonyl's oxygen, and the agostic complex 5b is also less stable than 5a based on the energy calculation (MOE).…”
Section: Resultsmentioning
confidence: 99%
“…less than one atmosphere of isotopic gas), and the ability to yield products of high purity with tolerance of many important functional groups [60].…”
Section: Heterogeneous Metal-catalyzedmentioning
confidence: 99%
“…All three are reasonably air/moisture stable bright‐red crystalline solids, and have been tested and subsequently utilized with a range of pharmaceutical drug candidates. One of the most widely utilized pre‐catalysts [(cod)Ir(PPh 3 ) 2 ]BF 4 ( 2 ) was shown in one study7 to be slightly more efficient than [IrH 2 (PPh 3 ) 2 (CH 3 COCH 3 ) 2 ]BF 4 . Complex ( 2 ) has also been shown to support H/D/T exchange labeling at sp 3 carbons of N,N ‐dialkylamides and has been used to label a range of complex substrates – termed as having multiple ancillary functional groups (Figure 4).…”
Section: Introductionmentioning
confidence: 99%
“…in ( 13 ) (Figure 18). 7 In other cases, complete survival of the olefin occurs as in labeling of compounds ( 14 ) and ( 15 )25 where Crabtree's catalyst was utilized.…”
Section: Introductionmentioning
confidence: 99%